Limitations of soil-applied non-microbial and microbial biostimulants in enhancing soil P turnover and recycled P fertilizer utilization - a study with and without plants - Herrmann, Michelle Natalie; Griffin, Lydia Grace; John, Rebecca; Mosquera-Rodríguez, Sergio F.; Nkebiwe, Peteh Mehdi; Chen, Xinping; Yang, Huaiyu; Müller, Torsten (Frontiers in Plant Science, 2024)
Phosphorus recovery from waste streams is a global concern due to open nutrient cycles. However, the reliability and efficiency of recycled P fertilizers are often low. Biostimulants (BS), as a potential enhancer of P availability in soil, could help to overcome current barriers using recycled P fertilizers. For this, a deeper understanding of the influence of BSs on soil P turnover and the interaction of BSs with plants is needed. We conducted an incubation and a pot trial with maize in which we tested nonmicrobial (humic acids and plant extracts) and microbial BSs (microbial consortia) in combination with two recycled fertilizers for their impact on soil P turnover, plant available P, and plant growth. BSs could not stimulate P turnover processes (phosphatase activity, microbial biomass P) and had a minor impact on calcium-acetate-lactate extractable P (CAL-P) in the incubation trial. Even though stimulation of microbial P turnover by the microbial consortium and humic acids in combination with the sewage sludge ash could be identified in the plant trial with maize, this was not reflected in the plant performance and soil P turnover processes. Concerning the recycled P fertilizers, the CAL-P content in soil was not a reliable predictor of plant performance with both products resulting in